Light sheet microscopy and live imaging of plants - Berthet, Béatrice; Maizel, Alexis (Journal of microscopy, 2016)
Light sheet fluorescence microscopy (LSFM) is increasingly used to investigate biological processes in animals as well as in plants. LSFM achieves optical sectioning by the selective illumination of a single plane of the sample with a sheet of laser light while simultaneously recording emitted fluorescence orthogonally to the illumination plane. A 3D image of the sample can then be generated with a temporal resolution ranging from seconds to several days, and at scales ranging from subcellular to whole organ. By design, LSFM provides fast imaging, and low phototoxicity, two key criteria for live imaging under physiological conditions. Despite its potential, LSFM remains underutilized in plant biology. This review aims to highlight challenges of live imaging in plants, to describe key steps in using LSFM on live plant samples and finally at providing an overview of published examples of applications of LSFM in plants.